(untitled) (Research, Society and Development, 2022)
Objective: To determine from a literature review the pedagogical functionality of fables in the teaching and acquisition process of Libras in deaf students. Methodology: Qualitative, exploratory and descriptive research, using a literature review carried out by consulting online research databases such as Scielo (Scientific Electronic Library OnLine), ERIC (Education Resources Information Center) and Google academic. We selected 10 articles in Portuguese, between the years 1983 until 2021. Results: Fables are classified as the first literary genre in the narrative approach, therefore, fables stand out for proposing moral and ethical teachings or advice to assist in resolving conflicts. Literature provides the formation of a sense of identity, an interest in reading and serves as a tool to help the deaf in cognitive development, in addition to assisting in social inclusion, favoring the interpersonal interaction of the deaf with the non-deaf community. Conclusion: The lack of adaptive methodologies in order to improve the teaching and learning of people with deafness was notorious. Some students were exposed only to listening literature, and with little contact with literature itself. Thus, fables have great relevance in proposing a playful, pleasurable teaching and assisting in critical and reflective thinking.